2014
DOI: 10.1080/0965156x.2014.988496
|View full text |Cite
|
Sign up to set email alerts
|

Policies Against Poverty in Russia – A Female Responsibility

Abstract: This article analyses how social policies in Russia can give poor people opportunities to improve their life situations given the persisting norms of a moral and practical female responsibility for social welfare. Women working in the social sphere have created their own support networks for helping people to take part in state programmes and to become entitled to support in one way or the other. Their agenda is clearly larger than the directives they might be subject to from above. They use relations to creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…Social mothers' ability to promote welfare development thus depends on their capacity to transform whatever income or assets they have into useful necessities for the poor. As a result of the low priority given to femaledominated sectors in state policy, women have had to develop entrepreneurial skills, and these skills have survived after the Soviet system (Sätre 2014b;. Women use them in their formal positions as responsible for social policy and in informal positions, when taking responsibility voluntarily in social work.…”
Section: Women's Agency To Deal With Their Continued Responsibility F...mentioning
confidence: 99%
“…Social mothers' ability to promote welfare development thus depends on their capacity to transform whatever income or assets they have into useful necessities for the poor. As a result of the low priority given to femaledominated sectors in state policy, women have had to develop entrepreneurial skills, and these skills have survived after the Soviet system (Sätre 2014b;. Women use them in their formal positions as responsible for social policy and in informal positions, when taking responsibility voluntarily in social work.…”
Section: Women's Agency To Deal With Their Continued Responsibility F...mentioning
confidence: 99%
“…Here, we find the survival of entrepreneurial behaviour dealing with shortcomings resulting from the low-priority status of social issues in the Soviet system. Data from both Archangelsk and Nizhegorodskaya Oblast show that such shortcomings were solved by women's horizontally organized informal networks of mutual support or care (Sätre, 2014b).…”
mentioning
confidence: 99%
“…Although social policy partly continues to be financed by the state, it is organized in a new way. It is indicated that women who are responsible for social welfare have to find sponsors by themselves, for their regular activities (Sätre, 2014b(Sätre, , 2014c. Being responsible for organizing social welfare, women working in the social sphere have created their own support networks for this.…”
mentioning
confidence: 99%
See 1 more Smart Citation